2016
DOI: 10.3402/gha.v9.32486
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the competencies of primary health care clinic nursing managers in two South African provinces

Abstract: BackgroundManagerial competencies to enhance individual and organisational performance have gained currency in global efforts to strengthen health systems. Competent managers are essential in the implementation of primary health care (PHC) reforms that aim to achieve universal health coverage.ObjectiveTo evaluate the competencies of PHC clinic nursing managers in two South African provinces.DesignA cross-sectional study was conducted in two South African provinces. Using stratified random sampling, 111 PHC cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 43 publications
7
34
1
2
Order By: Relevance
“…This study found that PHC managers in Timor‐Leste are not competent in problem solving on financial management in their jobs. The finding was similar to the studies conducted in South Africa and Saudi Arabia…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study found that PHC managers in Timor‐Leste are not competent in problem solving on financial management in their jobs. The finding was similar to the studies conducted in South Africa and Saudi Arabia…”
Section: Discussionsupporting
confidence: 91%
“…527 F I G U R E 1 The hypothesized seven-factor model (column 1) and five models' candidate (columns [2][3][4][5][6] found that PHC managers in Timor-Leste are not competent in problem solving on financial management in their jobs. The finding was similar to the studies conducted in South Africa 40 and Saudi Arabia. 38 Similarly, other studies argued that the lack of financial management competency is the fundamental cause of problems in financial management.…”
Section: Discussionsupporting
confidence: 91%
“…Researchers worldwide emphasize the importance of education and training as tools for improvement of core managerial competencies [15]. A study of nursing manager competencies from South Africa determined that even if the nursing managers have the experience, there is still a need for their continued professional education [16]. This type of education with specific aims could improve competencies, reduce the competency gaps and improve the decision-making process by upgrading skills in finding and using adequate information or research evidence [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years, there has been a growing focus on measuring competencies and performances in health care. Competencies are an integrated set of knowledge, skills, attitudes, and behaviors that one individual possesses, which enable effective performance of tasks and activities in certain occupations or functions in various complex situations [14][15][16][17][18][19][20][21]. Systematic measurement is important for the continuous progress of quality in health care, best management practice use, and management educations design [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation